THE ROLE OF FEMINIST JURISPRUDENCE IN LEGAL THOUGT - Laila Muhammad Rasyid; Fanny Tasyifa Mahdy (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2022)
This research aims to study the feminist concept as an entity in the process of forming a view of law and justice. With a normative -sociological approach, where data is obtained from the study of legal texts, expert opinions, and various other sources related to this topic. The results of the study show that the birth of male dominance in the thought process of legal formation, because male groups have misunderstood or biased in constructing the concept of man. According to feminists, legal structures are created by men and reinforce male values. By stating that the male group is the norm. Conversely, women are deviations from the norm and this is hegemony in the concept and reinforcement of patriarchal law and power. Feminists challenge and dismantle the belief or myth that men and women are so different, that certain behaviours can be distinguished on the basis of gender differences. Gender according to feminists is socially created or moulded not biologically. Sex determines physical appearance, reproductive capacity, but does not determine psychological, moral or social traits. Feminist legal theory or Feminist jurisprudence is a legal philosophy based on gender equality in the political, economic and social field